Invasive Spartina alterniflora in controlled cultivation: Environmental implications of converging future technologies. (November 2021) - Syed, Shameer; Xu, Min; Wang, Zaifeng; Yu, Chengfeng; Lian, Bin
Graphical abstract: Highlights: Not all invasive plants are unusable, Spartina alterniflora (SA) has multiple exploitable benefits. When utilized in controlled conditions SA's benefits significantly outweigh the implications. SA is an excellent biomass resource, CO2 sequestrator, and pollution remover. SA's soil restoration and resilience improvement potentials are effective in polluted or degraded soils. SA is an underrated plant species with multiple application potential. Abstract: Invasive species have become a major threat to ecosystem stability, diversity and sustainability in recent times. Invasive plants such as Spartina alterniflora (SA), outgrow resident flora by rapidly utilizing essential soil nutrients depriving the native plant species, impacting the ecosystem diversity and stability. SA is also notorious for its effect on local biodiversity as it grows and spreads faster, ultimately dominating local biodiversity. This dominance and the negative effect of invasive SA is due to features such as allochemical's secretion, positive feedback between plant and soil, and rapid absorption of soil nutrients, exerting a competitive advantage over native plants. Therefore, in this review, we aim to contemplate the implications and potential applications of SA under control conditions or special circumstances as a source of biomass, soil restorer, CO2 capture agent, soil resilience enhancer and pollution remover as most of the studies on SA have focused on controlling its impact on the local ecosystem. On the other hand, SA's ability to grow quickly in poor alkaline soils is useful but very little is explored to exploit SA for biomass production in controlled cultivation in different environmental conditions. In addition to these aspects, the CO2 sequestration capability requires greater focus, especially in sensitive salt marshes and wetlands along the coastal areas.